Characterisation and evaluation of the mechanical behaviour of endodontic-grade NiTi wires - Pereira, Samuel (2020)
With the introduction of new materials and advances in medical science, the endodontic files have changed since the early days of root canal treatments. In the late days, we have seen an increasing use of Nickel-Titanium (NiTi) alloys. At body temperature, NiTi alloys present a superelastic behaviour, which allows to be more effective in the removal of the tooth pulp tissue, and in the protection of the tooth structure. Anyhow, these NiTi instruments will eventually fracture, usually without any visual signal of degradation. Thus, there is a need of studying these alloys, as they present a high hysteresis cycle and non-linearities in the Elastic domain. Currently, there is no international standard to test NiTi endodontic files, so various authors have attempted to design systems that can test them under fatigue loads, usually based on empirical setups. Following a systematic approach, this work presents the results of rotary fatigue tests for two Alfa Aesar (R) Nitinol wires with different diameters (0.58mm and 0.25mm).The formulation is presented, where the material strength reduction can be quantified from the determination of the strain and the number of cycles until failure, as well numerical FEM simulation to verify the analytical model predictions.